PS4:69 Epidemiology of vascular primary antiphospholipid antibodies syndrome. (21st March 2018) - Nalli, C; Pascariello, G; Zentilin, A; Raffetti, E; Andreoli, L; Gasparotti, C; Magoni, M; Scarcella, C; Donato, F; Tincani, A
Abstract : Objective: Antiphospholipid Syndrome(APS)is a systemic autoimmune disease characterised by the presence of thrombotic and/or obstetrical manifestations and antiphospholipid antibodies (aPL). In 2006 were published the Sapporo criteria for APS but by now no epidemiological study on this disease were performed. Incidence and prevalence of primary APS(PAPS) are still unknown. The aim of this study was to evaluate the prevalence during the year 2013 and incidence for the period 2011–2015 of vascular PAPS in the adult population of a defined area, Valtrompia valley, using multiple sources. Valtrompia is a 40 kilometers-long prealpine valley in northern Italy. The population in 2013 was 101.477 inhabitants. The only easy access to the valley is from Brescia, the main city of the province. This valley is a cul-de-sac area without any other comfortable and practicable access. Therefore, this valley is ideal for epidemiological studies. In addition, the only Rheumatology referral tertiary Centre of the province is located in Brescia. This project was approved by the local Ethical Committee. Methods: We identified adult subjects of 18–50 years old living in Valtrompia. Patients with thrombotic events were identified by two sources: hospital demission code using key words (deep vein thrombosis, pulmonary embolism, myocardial infarction, ischaemic stroke); patients with defined diagnosis of vascular PAPS already followed by the Rheumatology tertiary Centre in Brescia. Results: We identified 47 patients with venous events during 2011–2015. 27/47 (57%) were tested for aPL, 4/27 (15%) positive. Regarding arterial events, 36 patients had stroke and 33/36 (92%) were tested for aPL, 4/33 (12%) positive. Finally, 64 patients with myocardial infarction (IMA): only 14/64 (22%) were tested for aPL, 2/14 (14%) positive. Table 1 shows incidence of vascular PAPS. Prevalence was 35.4 (95% CI: 20.6 to 59.6) per 100.000 inhabitants in 2013. Conclusions: Preliminary results of this study showed that PAPS is a rare disease and accurate epidemiological studies are necessary to better characterised patients. Another point is that aPL were not routinely tested in young subjects with vascular events, especially in patients with myocardial infarction. Results will be updated, we are going to recall patients never tested for aPL during the hospital admission.